Editorial: Volume 2, Issue 2 - Kristy L Archuleta; John E Grable (Journal of Financial Therapy, 2011)
This editorial started to take shape during the later part of November, right before Thanksgiving. The Thanksgiving break came and went quickly for the two of us, and before we knew it, December was here. In a moment of retrospective thinking, we stopped and thought about how this Journal has grown from a simple idea into something that is helping shape the emerging field of financial therapy in just a matter of one or two years. How grateful we are to be able to help guide this important outreach function of the Financial Therapy Association. Even though we get caught up in the day-to-day routines of teaching, conducting research, providing service to the profession, and working diligently to produce a world-class journal, we want every reader to know that we are honored to serve as editors and to be, in a minor sense, ambassadors for the financial therapy field.
Keywords: financial therapy